Saturn: the ringed beauty - Asimov, Isaac frey50 (Garth Stevens publishing Milwaukee, 1988)
Describes the physical characteristics, rings, moons, and movement of the planet Saturn.
Keywords: Saturn (Planet) -- Juvenile literature